History and future lines of urbanization process in Finland - Elli Heikkilä; Taru Järvinen (European Regional Science Association (ERSA), 2002)
Urbanization began in Finland relatively late by comparison with other European countries, but the process has taken place all the more rapidly. The population has concentrated to the southern part of Finland and there are nowadays only few growth centres. The purpose of this paper is to examine the process of urbanization over a long time span and light up the different scenarios of future population distribution. The number of cities and towns in Finland increased by 57 % between 1950 and 1998, but one notable feature of these cities and towns is their small size in terms of population, 86 % of them having less than 50 000 inhabitants and only 6 of them exceeding 100 000 inhabitants in 1998. According to forecasts the population will concentrate still in future in Finland. The proportion of people who are living in the built-up areas will be 84 % in 2005. Finland`s development is 15 years behind Sweden: Sweden reached this figure already in 1990. The population of the rural areas will continue to decrease in future. Population of Helsinki will grow up to 2020 by almost 68 000 persons. The population level will be then 611 361 inhabitants.
Keywords: 330